Jurisprudence in Shari'ah Policy (Applied Models (Journal of the College of Basic Education, 2020)
This research is concerned with studying the jurisprudence of budgets and explaining its importance and impact in the deducted Shariah rulings that accept flexibility according to interests and evils, and it shows and evidence for it from the Holy Qur’an, the Prophet’s Sunnah, consensus and reason, and then takes the applied models from the jurisprudence of Shariah policy in the era of the Messenger (peace be upon him) and the era of caliphs The adults (may God be pleased with them) and the jurists.The research also shows the effect of the science of budget jurisprudence on the legal policy in a significant and widely used way, especially since the legal policy is adopted by rulers and governors in the conduct of the affairs of the state, and they are exposed to issues that require weighting between opposing interests such as the public interest and the private interest, such as preserving religion and preserving the rest of the affairs The state, and our scholars and scholars mentioned this and gave examples of it, and they gave solutions through studying them in the jurisprudence of budgets, based on that to the Holy Qur’an and the actions of the Prophet (peace and blessings of God be upon him and God) in such matters and reliance on jurisprudential rules, or weighting between a Interests to achieve major interests and public benefits